2022
DOI: 10.3389/fnagi.2022.788322
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chronic Hypoxic Environment on Cognitive Function and Neuroimaging Measures in a High-Altitude Population

Abstract: ObjectiveThis study aimed to investigate the effects of long-term hypoxic environment exposure on cognitive ability and neuroimaging characteristics in a highland population in China.MethodsHealth system workers in Maduo County (4,300 m above sea level) and Minhe County (1,700 m above sea level) were selected as research participants and divided into a high-altitude (HA) group and low-altitude (LA) group, respectively. Cognitive ability was assessed using the Montreal Cognitive Assessment (MoCA), Verbal Fluenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…They found that the ALFF was reduced in the left cerebellum, right anterior cuneiform lobe, and left posterior central/supramarginal gyrus (PostC) in patients with PD, and a greater decrease in the ALFF was observed in the left pallidum and anterior central gyrus/PostC, and the left caudate nucleus/putamen showed a positive correlation with the disease course, similar to some results of the current study. Zhang et al (2022) found that chronic hypoxia can lead to extensive cognitive impairment, in addition to a significant reduction in the ROI density of the left olfactory cortex, right medial superior orbitofrontal gyrus, bilateral insular lobes, left globus pallidus and temporal lobe. These findings also support the idea that changes in orbitofrontal gyrus brain function may be a promising imaging marker in Parkinson’s disease, consistent with our idea.…”
Section: Discussionmentioning
confidence: 95%
“…They found that the ALFF was reduced in the left cerebellum, right anterior cuneiform lobe, and left posterior central/supramarginal gyrus (PostC) in patients with PD, and a greater decrease in the ALFF was observed in the left pallidum and anterior central gyrus/PostC, and the left caudate nucleus/putamen showed a positive correlation with the disease course, similar to some results of the current study. Zhang et al (2022) found that chronic hypoxia can lead to extensive cognitive impairment, in addition to a significant reduction in the ROI density of the left olfactory cortex, right medial superior orbitofrontal gyrus, bilateral insular lobes, left globus pallidus and temporal lobe. These findings also support the idea that changes in orbitofrontal gyrus brain function may be a promising imaging marker in Parkinson’s disease, consistent with our idea.…”
Section: Discussionmentioning
confidence: 95%
“…Another study by the same team found that Tibetans who lived at high altitudes for a long time had increased GM volume in the visual cortex, hippocampus and rectus (36). Another study showed that the GM volume in HA residents is significantly higher than LA residents in the bilateral somatosensory cortex and vision cortex (37) superior frontal gyrus, bilateral insula, left globus pallidus, and temporal lobe (28). Feng et al's observation of healthy people who migrated to Lhasa (3,658 m) for 2 years, showed that no significant change in total GM volume compared with the SL group, but there were decreased regional GM volume in the HA group, such as putamen, insula, amygdala, pale nucleus, hippocampus, amygdala (40).…”
Section: Main Outcomes and Meta-analysis Gmmentioning
confidence: 98%
“…In terms of ReHo analysis, the included studies produced inconsistent results. Zhang et al found no significant difference in ReHo values between highaltitude HA group and LA group (28,36). However, Chen et al reported ReHo increased significantly in bilateral hippocampus, and decreased significantly in bilateral putamen, bilateral superior temporal gyrus, and medial frontal gyrus, after prolonged exposure to high-altitude (42).…”
Section: Brain Function and Hamentioning
confidence: 99%
See 2 more Smart Citations